Семантическое аннотирование в информационно-поисковых системах - Дударь, З. В.; Егоров, С. В. (ХНУРЭ, 2013)
Проведен анализ структуры информационно-поисковых систем, в основу работы которых положена концепция инвертированного индекса. Рассмотрены наиболее эффективные методы аннотирования текста. Предложен метод поэтапного информационного поиска, позволяющий расширить возможности пользователя и сократить время, затрачиваемое им на поиск необходимой информации. Method of step-by-step information retrieval which will help to enlarge user possibilities while searching for necessary information and dramatically decrease search time was proposed in the work. Method provides for giving an annotation and reference to location of source text per user’s request. By results of brief review of the annotation user can make decision of necessity of full original text viewing.
Keywords: инвертированныый индекс; информационно-поисковые системы; семантическое сжатие